Introduction to the special issue: perspectives on research libraries. Issue 2 (2014) - ,; ,; ,
Abstract : Purpose – The aim of this article is to introduce the special issue of Journal of Documentation focusing on perspectives on research libraries.Design/methodology/approach – The paper outlines the theme of the issue and its underlying problems.Findings – The traditional services of research libraries may diffuse to other kinds of institutions. There is, however, a need for information specialists studying and improving research infrastructures. Future services probably need to be more focused, domain‐specific and based on research in information science.Originality/value – The introduction is written to assist readers surveying the issue and to share the thoughts of the editors in planning the issue. Acknowledgements : This thematic issue is part of a research project funded by the Danish Ministry of Culture in 2011‐2012. Apart from this issue, the research of the project has been reported in an anthology: Viden i spil – forskningsbibliotekers funktioner i forandring (English tr.: "Co‐creators of knowledge. The changing functions of research libraries", b4 Høyrup et al., 2012 ), and a thematic issue of a Danish library journal (b3 Hjørland and Høyrup, 2009 ). The authors thank the research council of the Ministry of Culture for their support.